A proposed methodology for preparing questions in social studies grade six teaching materials - Manzano, Wilhelmina Bucaneg 1943- (University of the Philippines, 1974)
This study proposed a methodology in the preparation of questions in Social Studies Grade Six teaching material. It investigated the kind of questions that are asked in Social Studies teaching materials, how such questions are prepared and how they are included in the teaching material.